Politics and Literary Form in the Last Quarter of the Twentieth Century - Antunes, Benedito [UNESP] (FapUNIFESP (SciELO), 2021)
This paper analyses Um copo de co´lera (1978), by Raduan Nassar, and Estorvo (1991), by Chico Buarque, aiming to observe the possible relationship between Romanesque form and political conflicts of the last quarter of the 20th century in Brazil. The paper hypothesizes that the elements recalled in the books literarily reach a deadlock which refers to an external context, gaining, in that movement, an esthetical perception of the period. Therefore, it is a dialectic reading attempt, in the same way proposed by Antonio Candido and Robert Schwartz, in which one tries to approximate the social form to the literary one, aiming at establishing perspectives of understanding, as much for one as for the other. As a result, the analysis suggests a process of disorientation in the quest for social transformation.
Poli´tica e forma litera´ria no u´ltimo quartel do se´culo XX
Keywords: Chico Buarque; Contemporary Brazilian novel; literature and history; Raduan Nassar